Why Worry About Tax Expenditure? - Swift, Zhicheng Li; Cavalcanti, Carlos B. (World Bank, Washington, DC, 2012)
Tax expenditures are concessions that fall outside tax norms or benchmarks. These norms include accounting conventions, the structure of tax rates, the deductibility of compulsory payments, provisions to facilitate tax administration, and norms related to international fiscal obligations. Tax expenditures are deviations from these norms, implemented to encourage behavior deemed desirable by policymakers, and can take a number of forms-including tax exemptions, allowances, credits, deferrals, and relief (see OECD 1996). The classic example is a tax deduction for charitable contributions, where the reduction in tax revenue is more than offset by the increase in support for charitable activities. Tax expenditures are not a free lunch, however. They can lead to inefficiencies and inequities, stimulating no additional activity and making the tax regime more regressive. For instance, a tax concession granted to employers who hire unskilled workers might go to employers who would have hired such workers anyway. Tax expenditures also affect government budgets, because they imply forgoing revenue that could be used to fund direct government expenditures.